Effects of Hst3p inhibition in Candida albicans: a genome-wide H3K56 acetylation analysis - Conte, Marisa; Eletto, Daniela; Pannetta, Martina; Petrone, Anna M.; Monti, Maria C.; Cassiano, Chiara; Giurato, Giorgio; Rizzo, Francesca; Tessarz, Peter; Petrella, Antonello; Tosco, Alessandra; Porta, Amalia (Frontiers in Cellular and Infection Microbiology, 2022)
Candida spp. represent the third most frequent worldwide cause of infection in Intensive Care Units with a mortality rate of almost 40%. The classes of antifungals currently available include azoles, polyenes, echinocandins, pyrimidine derivatives, and allylamines. However, the therapeutical options for the treatment of candidiasis are drastically reduced by the increasing antifungal resistance. The growing need for a more targeted antifungal therapy is limited by the concern of finding molecules that specifically recognize the microbial cell without damaging the host. Epigenetic writers and erasers have emerged as promising targets in different contexts, including the treatment of fungal infections. In C. albicans, Hst3p, a sirtuin that deacetylates H3K56ac, represents an attractive antifungal target as it is essential for the fungus viability and virulence. Although the relevance of such epigenetic regulator is documented for the development of new antifungal therapies, the molecular mechanism behind Hst3p-mediated epigenetic regulation remains unrevealed. Here, we provide the first genome-wide profiling of H3K56ac in C. albicans resulting in H3K56ac enriched regions associated with Candida sp. pathogenicity. Upon Hst3p inhibition, 447 regions gain H3K56ac. Importantly, these genomic areas contain genes encoding for adhesin proteins, degradative enzymes, and white-opaque switching. Moreover, our RNA-seq analysis revealed 1330 upregulated and 1081 downregulated transcripts upon Hst3p inhibition, and among them, we identified 87 genes whose transcriptional increase well correlates with the enrichment of H3K56 acetylation on their promoters, including some well-known regulators of phenotypic switching and virulence. Based on our evidence, Hst3p is an appealing target for the development of new potential antifungal drugs.